2015
DOI: 10.1007/s10661-015-4925-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of nutrient emission from intensive cage aquaculture on the semiarid reservoir water quality

Abstract: The effects of cage aquaculture on freshwater ecosystems are determined by multiple farming and environmental variables, and thus, the assessment of a wide range of abiotic and biotic variables enables better understanding of the impacts generated by this nutrient source. This study was carried out at Castanhão reservoir located in the State of Ceará, which is the largest Brazilian producer of Nile tilapia in cage systems, wherein about 8000 reservoirs provide a vast area to expand not only this important soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
2
13
0
5
Order By: Relevance
“…The comparison between estimates of the natural and anthropogenic nutrient loads to the watershed of the Castanhão reservoir indicates that anthropogenic sources correspond to almost all emissions of nitrogen and phosphorus to the reservoir (Table I). Therefore, changes of trophic state of the reservoir are directly associated with the occupation of its drainage basin and the type and intensity of activities carried out within the reservoir, in particular fish farming (Barbosa et al 2012, Molisani et al 2015. A significant fraction of the total nutrients load to the basin is retained in soils prior to reaching the Castanhão Reservoir.…”
Section: Nutrient Emissions To the Castanhão Reservoirmentioning
confidence: 99%
“…The comparison between estimates of the natural and anthropogenic nutrient loads to the watershed of the Castanhão reservoir indicates that anthropogenic sources correspond to almost all emissions of nitrogen and phosphorus to the reservoir (Table I). Therefore, changes of trophic state of the reservoir are directly associated with the occupation of its drainage basin and the type and intensity of activities carried out within the reservoir, in particular fish farming (Barbosa et al 2012, Molisani et al 2015. A significant fraction of the total nutrients load to the basin is retained in soils prior to reaching the Castanhão Reservoir.…”
Section: Nutrient Emissions To the Castanhão Reservoirmentioning
confidence: 99%
“…Since droughts are increasing in frequency and severity in many regions such as in tropical semi-arid areas (Marengo et al, 2013;Marengo and Bernasconi, 2015), this study may give us clues to understanding the effect of climate change on phytoplankton of artificial reservoirs. These systems play fundamental roles in the Brazilian semi-arid due their multiple uses as drinking water supply and intensive fish-cage aquaculture sites (Cirilo, 2008;Molisani et al, 2015).…”
Section: Assessing Temporal and Spatial Variability Of Phytoplankton mentioning
confidence: 99%
“…Afterwards, apart from continuing accumulation, and extra enrichment of nutrients was due to breaking thermal stratification, mixing of the water column (Groups 2A, 2B), and at least in the shallowest stations (Group 2B) sediment resuspension. Molisani et al (2015) reported, based on stable C and N distribution, current velocities and deposition rates of fecal pellets, that effluents from cage aquaculture (feed and feces) were not extensively reaching the water column and the bottom sediments of the cage area, on the contrary, effluents from farms are carried out to the deeper, central region of the reservoir. Hydrodynamic modeling of the reservoir (Molisani et al, 2015;Oliveira et al, 2015) showed surface wind-drive currents to move westwards from the center deeper part of the reservoir to shore, whereas bottom currents flush-out fish farm areas and incoming runoff eastwards to the deeper regions (Group 1 region), where stratification exists during high volume periods (e.g., in station 6 in November, 2011 -Supplementary Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, by comparing the emission of a single farm (67 t production) with the total N contribution from the watershed, Molisani et al (2015) reached the conclusion that fish farming contributes relatively little to the total N inputs to the reservoir. When extrapolated to the entire fish production of the reservoir, however, this activity is the largest direct contributor of N and P to the reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation